2020
DOI: 10.1038/s41598-020-63837-4
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding Silver Butter Catfish (Schilbe intermedius) Reveals Patterns of Mitochondrial Genetic Diversity Across African River Systems

Abstract: The silver butter catfish (Schilbe intermedius) is widely distributed across African river systems. To date, information on its mitochondrial genetic diversity, population structure, and historical demography are not well-established. Herein, we combined newly generated mitochondrial cytochrome c oxidase (COI) subunit I gene sequences with previously published COI sequences in the global databases to reconstruct its phylogeography, population genetic structure, and historical demography. Results from the mtDNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
(63 reference statements)
1
10
1
Order By: Relevance
“…Correct identification of morphologically similar species is essential for fisheries management and biodiversity documentation (Amanda & Luciane, 2010). Recent studies on Nigerian freshwater fishes showed that genetic data, in combination with morphological data, could aid accurate and unambiguous identification of the fish species (Nneji et al ., 2020; Oladipo et al ., 2020; Uden et al ., 2020). The application of molecular tools, involving mitochondrial cytochrome c oxidase subunit I ( COI ), has contributed significantly to fish systematics (Iyiola et al ., 2018; Nwani et al ., 2011; Oladipo et al ., 2020).…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…Correct identification of morphologically similar species is essential for fisheries management and biodiversity documentation (Amanda & Luciane, 2010). Recent studies on Nigerian freshwater fishes showed that genetic data, in combination with morphological data, could aid accurate and unambiguous identification of the fish species (Nneji et al ., 2020; Oladipo et al ., 2020; Uden et al ., 2020). The application of molecular tools, involving mitochondrial cytochrome c oxidase subunit I ( COI ), has contributed significantly to fish systematics (Iyiola et al ., 2018; Nwani et al ., 2011; Oladipo et al ., 2020).…”
Section: Figurementioning
confidence: 99%
“…This method, commonly referred to as DNA barcoding, has been successfully used to resolve species‐level placement, especially in cases where conventional methods may result in ambiguities (Abdullah & Rehbein, 2017; Hubert et al ., 2008). Currently, DNA barcoding has been advocated as a useful tool for the species identification of various life stages and identification of hidden diversity (Iyiola et al ., 2018; Nneji et al ., 2020; Ward et al ., 2005). Further, the mitochondrial COI gene has been used in elucidating phylogenetic relationships between and within fish species (Iyiola et al ., 2018; Nneji et al ., 2020; Uden et al ., 2020).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…For fish, the research project Fish Barcode of Life Initiative (FISH-BOL), launched in 2005 [ 21 ], is probably the most important initiative that not only increased the amount of reference sequences on a global scale, but also provided laboratory protocols, alternative primer cocktails and suggestions to overcome failures [ 22 , 23 ]. Identification of fish species by DNA barcoding has been applied in several contexts [ 24 , 25 , 26 , 27 ] and has also been used to certificate the authenticity of fish species by detecting species substitution on commercial markets [ 9 , 28 , 29 , 30 ]. Indeed, in the fields of seafood safety, DNA barcoding has earned itself a central role, demonstrating its potential for fast and reliable identification of frauds and is a valid method used by the US Food and Drug Administration for species identification of fish [ 31 ].…”
Section: Introductionmentioning
confidence: 99%